An attenuated temperature‐sensitive strain of cytomegalovirus (tsm5) establishes immunity without development of CD8+ T cell memory inflation. Issue 11 (12th July 2013) - Beswick, Mark; Pachnio, Annette; Al‐Ali, Abdulaziz; Sweet, Clive; Moss, Paul A.
Abstract Cytomegalovirus (CMV) is a widely prevalent herpesvirus that is well tolerated by an immune competent host yet establishes a state of chronic infection. The virus is thought to undergo frequent subclinical episodes of reactivation which leads to an unusually large accumulation of CMV‐specific CD8+ T lymphocytes in the peripheral blood, a phenomenon termed "memory inflation." The high magnitude of the CMV T cell response has been implicated in impaired immunity to heterologous pathogens such as EBV, influenza and West Nile virus. Here, using murine CMV (MCMV), we show that memory inflation of virus‐specific CD8+ T cells is avoided if mice are infected with a replication defective virus called temperature‐sensitive mutant 5 (tsm5), which carries an attenuating mutation within the DNA primase gene. Mice infected with tsm5 do generate primary T cell responses towards viral proteins but these do not amass to skew the memory repertoire of CD8+ T cells. Therefore, attenuation of the virus replication machinery may be valuable in future CMV vaccine designs because the virus remains immunogenic but does not contribute to CMV associated T cell immune senescence. J Med. Virol. 85:1968–1974, 2013. © 2013 Wiley Periodicals, Inc.